Geographical and temporal variations in availability of national price negotiated novel anticancer drugs: a spatial statistical study based on two cross-sectional datasets in China - Ziqi Zhao; Shengwei Zhang; Tao Zheng; Ming Hu (Frontiers in Pharmacology)
ObjectiveThe National Drug Price Negotiation (NDPN) has significantly reduced the prices and improved the nationwide availability of novel anticancer drugs (NADs) in China. However, geographical disparities in their availability remain concerning. This study aims to assess these spatial variations and temporal changes, and the determinants using geographic information system (GIS) and spatial statistical methods.MethodsTwo cross-sectional datasets were used corresponding the implementation date of the 2023 NDPN list (1 January 2024) and 9 months after (1 October 2024). Data on drug-providing institutions were extracted from National Healthcare Security Administration (NHSA) platform. Drug availability was measured by the weighted supply number of drug-providing institutions per 1,000 cancer patients, analyzed separately for hospitals and retail pharmacies. Kernel density estimation (KDE) was used to visualize spatial distribution. The Theil index assessed inequality, and Moran’s index measured spatial clustering. Multiple linear regression (OLS) and geographically weighted regression (GWR) were employed to examine the influence of economic development and healthcare infrastructure on drug availability.ResultsA total of 71 NADs in the 2023 NDPN list were analyzed. By October, drug-providing institutions had become more concentrated in the eastern coastal provinces compared to January. Availability improved in both hospitals and retail pharmacies, with higher levels observed in eastern and central provinces, with lower in the western provinces, especially in the Southwest. Inequality declined and spatial clustering increased for both hospital-based and overall availability across provinces (Theil index, hospital: 0.074–0.062, overall: 0.045–0.044; Moran’s I, hospital: 0.315–0.362, overall: 0.452–0.453). Both OLS and GWR models showed a significant and strengthening association between availability (in hospitals and overall) and GDP per capita [e.g., hospital: OLS coef, 0.787–0.833, p < 0.001; GWR mean coef (SD), 0.795 (0.047)−0.834 (0.044); overall: OLS coef, 0.744–0.794, p < 0.01; GWR mean coef (SD), 0.726 (0.119)−0.763 (0.161)]. Retail pharmacy-based availability was positively associated with the number of local chain pharmacies [OLS coef, 0.098–0.122, p < 0.05; GWR mean coef (SD), 0.084 (0.006)−0.107 (0.010)].ConclusionThe availability of price-negotiated NADs increasingly concentrated in economically developed and medically advanced eastern provinces, while remaining lower in southwest. Efforts should target economically underdeveloped areas.